2015
DOI: 10.1016/j.jacc.2015.08.030
|View full text |Cite|
|
Sign up to set email alerts
|

Cardiorespiratory Fitness in Middle Age and Health Care Costs in Later Life

Abstract: Higher cardiorespiratory fitness in middle age is strongly associated with lower health care costs at an average of 22 years later in life, independent of cardiovascular risk factors. These findings may have important implications for health policies directed at improving physical fitness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
39
0
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 38 publications
3
39
0
11
Order By: Relevance
“…did not focus on CVD, our results seem to be in line with their findings, with −$723 as the difference between optimal PA versus nonoptimal PA in the multivariate model, in the general population. Another recent study analyzed costs related to PA using the Cooper Center Longitudinal Study (CCLS) . They found that expenditures in later life (≥65 years of age) were greatly diminished if cardiorespiratory fitness was achieved in midlife years (around 50 years of age).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…did not focus on CVD, our results seem to be in line with their findings, with −$723 as the difference between optimal PA versus nonoptimal PA in the multivariate model, in the general population. Another recent study analyzed costs related to PA using the Cooper Center Longitudinal Study (CCLS) . They found that expenditures in later life (≥65 years of age) were greatly diminished if cardiorespiratory fitness was achieved in midlife years (around 50 years of age).…”
Section: Discussionmentioning
confidence: 99%
“…Past reports have described the relationship between some level of PA and costs 13,17,19,20,22,31 ; however, none have recently shown this on the basis of CVD, 16 with a focus on CRFs. This study provides current estimates from a nationally representative sample of the US population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, it has been demonstrated that adequate levels of cardiorespiratory fitness in adults have a strong association with lower public health care costs during the last period of life [22].…”
Section: Changes In Physical Fitness Throughout Human Life Spanmentioning
confidence: 99%